Phosphate modulated permeability of mesoporous silica spheres: a biomimetic ion channel decorated compartment model. Issue 2 (13th November 2014) - Liu, Wei; Liu, Jianbo; Yang, Xiaohai; Wang, Kemin; Wang, Qing; Yang, Meng; Li, Li; Song, Chunxia
Abstract : Surface amine group functionalized mesoporous silica sphere was developed as a biomimetic compartment model, in which the ion permeability through the gatekeeper shell can be well modulated via the external phosphate ion. Abstract : Due to their high loading capacity, permeability modulation, and biological compatibility, mesoporous silica spheres provide a suitable system for mimicking cellular compartments. Herein, a surface amine group functionalized mesoporous silica sphere was developed as a biomimetic compartment model, in which the ion permeability could be well modulated through the external phosphate ion. The amine group was selectively modified on the surface of the mesoporous silica sphere in the presence of a template molecule (CTAB) in the mesochannel. The surface amine group was employed as a gatekeeper shell and the specific binding of the anionic phosphate with the amine groups reversed the surface charge from positive to negative and gated the permeability of the model cationic Ru(bipy)3 2+ . Ion channel decorated compartment is one of the key architectual principles of the cell, which maintains a high local reagent concentration inside it via the high surface area interior, and its permeability is tuned by a collection of ligand-gated ion channels outside to ensure a metabolic balance. The permeability modulation in the mesoporous silica sphere closely resembles that observed in a biological ion channel decorated compartment in vivo . This protocol provides the possibility of simulating the process of ion permeability in biological compartments based on mesoporous silica spheres, and it also contributes to the design of artificial cells and bio-inspired responsive nanoreactors.